The Sky at Night - Moore, Patrick. (Springer New York : Imprint: Springer, 2010)
For more than 50 years now Sir Patrick Moore has presented the BBC Television series Sky at Night; not a month has been missed – a record for any television series, and a record which may never be broken. Every three years or so a book is published covering the main events in both astronomy and space research. This is the 13th volume, not only a record of the programmes but also of the great advances and discoveries during the period covered - eclipses, comets, and the strange chemical lakes of Titan, for instance, but also anniversaries such as the fifteenth “birthday” of the Hubble Space Telescope, and not forgetting the programme celebrating the Sky at Night’s 50th year, attended by astronaut Piers Sellars and many others who appeared on the programme over the years. All the chapters are self-contained, and fully illustrated. In this new Sky at Night book you will find much to entertain you. It will appeal to amateurs and professionals alike.